The role of religion and social capital on employees' performance: An empirical study post Indonesia's Islamic bank merger - Dyan Fauziah Suryadi; Mahlia Muis; Muh. Idrus Taba; Wardani Hakim (Cogent Business & Management, 2023)
The rapid development technology and information competition resulted companies to switch their strategies and operations including merger to obtain competitive advantage. Despite, the most population is Muslim, compared to conventional bank, Islamic bank market share in Indonesia is still stagnant in 5%. This research investigates how employees' religiosity influences the mediator variables, such as structural, cognitive, and relational social capital, which subsequently influences Indonesian Islamic banking performance post-merger. The sample consists of 675 Islamic bank employees. Structural equation modelling (SEM) was used to test the research hypotheses through three studies. The empirical results indicate that religiosity positively affects employees' social capital, precisely when employees have frequent communication and interaction, which also has a strong correlation to employees' share language, value, trust, and reciprocity. Furthermore, mediator variables, such as structural, cognitive, and relational social capital, have a partial role in religiosity and employees' performance. This study was limited to Indonesian Islamic bank employees. Therefore, future studies are needed to analyze cross-regional, culture, organization, and religion. Bank managers and regulators need to enhance employees' religiosity and social capital toward valuable communication and interaction. They also need to enlighten employees from the perspective of business and organization. This study contributes to human resource management and organization literature and the decision-making process associated with developing and testing a model of religious determinants of employees' performance towards social capital.
Keywords: 650; employees' performance; Indonesia's Islamic bank; post-merger; Religiosity; social capital